Pengaruh Media CORD-MAM Challenge terhadap Penguasaan Kosakata Bahasa Arab - Permatasari, Khoiriyah; Syarifuddin, Syarifuddin; Nurrokhmatulloh, Nurrokhmatulloh (Borneo Journal of Language and Education, 2025)
Vocabulary mastery is one of the crucial aspects in Arabic language learning that plays a role in improving students' language skills, both in understanding texts, writing, and speaking. However, in practice, many students experience difficulties in memorizing and understanding Arabic vocabulary due to learning methods that are still conventional, less interactive, and not interesting for students. The lack of using innovative learning media is also one of the factors that affect students' low vocabulary mastery. Therefore, this study aims to analyze the effectiveness of using CORD - MAM Challenge media in improving the mastery of Arabic vocabulary in grade V students of MI Mambaul Khoir Talang Prigen Pasuruan. This study used quantitative method with Pre-Experiment One Group Pre-test-Post-test design. The research subjects consisted of 27 students who were randomly selected as samples, Data were collected through observation, interview, pre-test and post-test to measure the level of vocabulary mastery before and after the application of media and documentation. The results showed a significant increase in students' vocabulary mastery after learning using this media. The average pre-test score of 67,78 increased to 83,15 in the post-test. The Paired Sample T-Test results showed a significance value of 0,00 (p < 0,05), which indicates a significant effect of using this media on improving student learning outcomes. This finding shows that the use of CORD - MAM Challenge in Arabic language learning is able to increase students' active involvement and create a more fun and interactive learning atmosphere. This challenge-based learning model not only helps students in remembering and understanding vocabulary better, but also increases their learning motivation. Therefore, this method can be used as an effective alternative in Arabic language learning, especially in teaching vocabulary at the primary school level.